Power elites and state-business relations: Malaysia-China selected belt and road initiative projects / Khaw Mooi Hock - Khaw , Mooi Hock (2021)
This study focuses on state-state-business ties, a new phenomenon shaped by how local power elites (LPEs) collaborate with Chinese transnational corporate elites (TCEs) to implement infrastructure projects related to China’s Belt and Road Initiative (BRI). These LPE-TCE links, in turn, have led to the creation of novel forms of state-business relations (SBRs), with diverse outcomes and implications. In Malaysia, these state-state-business ties, forged by both countries for their respective business enterprises, were primarily a consequence of an interesting confluence of two major events, which took place between 2014 and 2016: 1) Malaysia’s 1Malaysia Development Berhad (1MDB) scandal; and 2) the introduction of China’s BRI. These events then witnessed leaders of two single-dominant parties (SDPs), the United Malays National Organisation (UMNO) and Chinese Communist Party (CCP), coming together to pursue their respective economic and political objectives. This thesis draws attention to this important and new phenomenon that offers interesting theoretical insights in both elite- and SBR-related studies. The conventional wisdom of homogenised SBRs is built on, by indicating that, in practice, state-business ties are extremely heterogeneous. This study has developed a conceptual framework that explains how state-state-business ties, forged by two countries, both led by SDPs, that control their respective enterprises, have contributed to unique SBRs, created to undertake BRI projects, which in turn are driven by specific LPE-TCE links. Case studies are employed to trace empirically why the three BRI projects in Malaysia were implemented on a non-transparent basis. These studies provide insights into how disparate forms of SBR-based institutional architecture function, not only at the federal level, but also in different states in Malaysia, with links externally to Chinese enterprises. In the process, it draws attention to the emergence of diverse types of power and inter- and intra-elite relationship issues of different LPEs, like elite unity, elite contestation, and elite settlement, which have contributed to the creation of dissimilar SBRs. This study notes that different LPEs, as key actors in the state, might have turned effective and collaborative SBRs, fashioned to implement the three BRI projects, into economic endeavours that also feature ineffective and collusive relationships, characterised by rent-seeking behaviour. This study also highlights that key UMNO elites and Chinese state-owned enterprises (SOEs) appear to be central in these novel SBRs, an issue that has had major implications for the Malaysian economy, as well as its political system.